Association of contrast enhancement of proximal internal carotid artery wall and champagne bottle neck sign with ipsilateral stroke in moyamoya disease patients. Issue 155 (October 2022) - Zhou, Fei; Wang, Maoxue; Cao, Lei; Li, Xueping; Lu, Jiaming; Yang, Yongbo; Wang, Jian; Zhang, Xin; Zhang, Bing
Abstract: Objective: To investigate the characteristics of the proximal internal carotid artery (ICA) and their relationships with ipsilateral intracranial stroke in sufferers of moyamoya disease (MMD) with champagne bottle neck sign (CBNS). Patients and methods: Forty-four patients with MMD（mean age 43.98 ± 10.54 years, 21 males）confirmed by digital subtraction angiography were enrolled and carotid magnetic resonance vessel wall imaging was introduced in this study. CBNS was defined as the ratio of the diameters of proximal ICA to the common carotid artery (CCA) (DpICA/CCA) < 0.5. The wall thickness and enhancement of the proximal ICA was measured on postcontrast T1-VISTA images. The correlations between these characteristics of the proximal ICA and ipsilateral intracranial stroke were analysed. Results: Among the 44 patients with MMD, twelve patients (27.3 %) had bilateral CBNS and fourteen patients (31.8 %) without CBNS. Compared with normal extracranial arteries, in arteries with CBNS, the proximal ICA had a smaller diameter (3.03 ± 1.05 mm vs 3.95 ± 1.10 mm, p < 0.001), the maximum wall thickness of the proximal ICA was thicker (1.34 ± 0.31 mm vs 1.06 ± 0.26 mm, p < 0.001), and arterial wall contrast enhancement was more frequently observed (66.7 % vs 2 %, p = 0.001). Logistic regression analysis revealed that the wall enhancement of the proximal ICA with CBNS (OR = 15.16, 95 % CI, 2.32–99.02; P = 0.005) was independently associated with intracranial multiple lesions. The AUC of the wall enhancement of the proximal ICA with CBNS was 0.79(P = 0.003). Conclusions: Vessel wall enhancement of the proximal ICA with CBNS is independently associated with intracranial stroke in the ipsilateral hemispheres of patients with MMD, particularly those with multiple lesions.